Abnormal expression of Hippo–YAP1 signalling pathway and progesterone resistance mechanism in endometrial polyps - Xinyu Yu; Weijia Kong; Kaiyue Shang; Hongxin Xing; Wenjing Sun; Qianqian Li; Hui Zhang (Journal of Obstetrics and Gynaecology)
Background Endometrial polyps (EPs) are a localised hyperproliferative disorder of the endometrium, and its pathogenesis remains unclear. Progesterone resistance may influence the recurrence rate of progesterone-treated EPs. Expression of the Hippo–YAP1 signalling pathway has been studied in various diseases. However, few studies have explored their expression in EPs and association with progesterone resistance. Prolactin (PRL), a molecular marker of endometrial mesenchymal cell metaplasia, indirectly reflects progesterone action in vivo. This study aimed to explore the role of Hippo–YAP1 signalling pathway in EPs.Methods Endometrial tissue specimens obtained by surgical resection from 35 patients with a normal endometrium and 35 with EPs were collected between July 2023 and July 2024. Immunohistochemically, the expressions of mammalian STE20-like kinase 1 (MST1), Yes-associated protein 1 (YAP1), progesterone receptor (PR) and PRL in the normal endometrium and EPs tissues were detected.Results Compared to normal endometrial tissues, the expression of MST1 was relatively low in EPs (p < .05), while the total and nuclear expression of YAP1 was relatively high in EPs (p < .0001). The expression of PR in EPs tissues was significantly lower than that in normal endometrial tissues (p < .05), and the expression level of PRL was lower than that of normal endometrium in EPs tissues (p < .001).Conclusions EPs have progesterone resistance, and the Hippo–YAP1 signalling pathway may be involved in the development and progression of EPs by acting on the progesterone resistance mechanism.